A simple process to create micro-gaps in printed copper electrodes by sintering induced stress in flexible PET substrates. (24th May 2021) - Wu, Xinzhou; Yuan, Wei; Su, Wenming; Cui, Zheng; Zhu, Simeng; Deng, Ming
Abstract: A new simple low-cost technique for fabricating micro-gaps of less than 50 µ m in copper electrodes is reported, which combines conventional screen printing of copper paste and intense pulsed light (IPL) sintering. The micro-gap is created via a two-step IPL sintering. First, a continuous printed copper stripe is half sintered along its length with another half blocked by an opaque mask. Then, the second sintering is performed over the entire length of copper stripe with the opaque mask removed. At the joint between two sintering steps, a micro-gap is formed across the copper stripe due to thermal contraction of underlying polyethylene terephthalate substrate. The width of copper micro-gaps can be adjusted by IPL energy. Simple light emitting diode circuits have been made by the micro-gap electrodes, demonstrating its feasibility for practical applications.